Design and implementation of IOT gateway based on embedded μTenux operating system. (2017) - Yao, Xiaofeng; Wang, Lei
Among the three layers of the Internet of Things (IoT), perceptual layer and network layer belong to the heterogeneous network, which can't communicate directly; they need an IoT gateway to realise the communication protocol conversion between the two layers. Because the gateway does not have a unified standard in the field of IoT, the gateway of each manufacturer has certain limitations. In this paper, combining actual gateway requirements definition in the network, small intelligent gateway was accomplished based on an OSI model that integrated ZigBee and TCP/IP protocols. The gateway provides Wi-Fi control interface for the user, and supports OTA, risk management and behaviour analysis operation etc. The STM32F439NI development board of ST company was adopted as the test platform, and the test was completed through cooperating with the Wi-Fi module and the ZigBee module. The results indicate that the design has better stability and higher performance.